2008
DOI: 10.2172/969183
|View full text |Cite
|
Sign up to set email alerts
|

Interim Report: 100-NR-2 Apatite Treatability Test: Low Concentration Calcium Citrate-Phosphate Solution Injection for In Situ Strontium-90 Immobilization

Abstract: SummaryEfforts to reduce the flux of strontium-90 ( 90 Sr) to the Columbia River from past-practice liquid waste disposal sites have been underway since the early 1990s in the 100-N Area at the Hanford Site. Termination of all liquid discharges to the ground in 1993 was a major step toward meeting this goal. However, 90 Sr adsorbed on aquifer solids beneath the liquid waste disposal sites and extending beneath the near-shore riverbed remains a continuing source to groundwater and the Columbia River. Researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…Comparing test results from these two locations indicated that the permeability contrast between the Hanford and Ringold Formations was significantly less over the upstream-most one third of the barrier. Williams et al (2008) estimated hydraulic conductivity for the Hanford and Ringold Formations over the upstream portion of the barrier at 12 and 10 m/day (39 and 33 ft/day), respectively. By contrast, hydraulic conductivity for the Hanford and Ringold Formations over the downstream portion of the barrier was estimated at 29 and 9 m/day (95 and 30 ft/day), respectively.…”
Section: 3mentioning
confidence: 99%
See 4 more Smart Citations
“…Comparing test results from these two locations indicated that the permeability contrast between the Hanford and Ringold Formations was significantly less over the upstream-most one third of the barrier. Williams et al (2008) estimated hydraulic conductivity for the Hanford and Ringold Formations over the upstream portion of the barrier at 12 and 10 m/day (39 and 33 ft/day), respectively. By contrast, hydraulic conductivity for the Hanford and Ringold Formations over the downstream portion of the barrier was estimated at 29 and 9 m/day (95 and 30 ft/day), respectively.…”
Section: 3mentioning
confidence: 99%
“…Springs, seeps, and subsurface discharge along the riverbank are the primary pathway of 100-N Area groundwater contaminants to the Columbia River. Additional details about the extent of seasonal and daily changes in river stage at the site from PRD discharge are reported by Williams et al (2008). …”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations